Sedimentary Facies of the Mahakam Delta: Comparison between the Modern and the Miocene - A. Wiweko; B. Giriansyah (Berita Sedimentologi, 1999)
The Mahakam Delta is located on the eastern coast of Kalimantan Island, some 50 km south of the equator. The coastline of this area is oriented NNE-SSW, and is open to the Makassar Straits which are about 200 km wide, separating Kalimantan and Sulawesi.Field studies in the modern Mahakam Delta have been conducted by several workers. G.P. Allen, in 1974, conducted fieldwork to acquire a preliminary understanding of the sedimentary framework and characteistic facies distribution. The work was based on field observation, sediment sampling by using a Berthois hand dredge (surface sediment sampling) and coring devices (up to 2-4 meters depth), and water samples. In 1975, a second phase of study was conducted involving a coring program on the modern Mahakam Delta. The objective was to study the major geometrical characteristics and facies patterns of the formations. Additional coring program was conducted in 1976, which consisted of a number of shallower auger holes of up to 10 metres depth, and surface sediment samples. Allen (1992) conducted fieldwork in the large mouth bar system adjacent to Muara Bujit. The study was based on surface sediment sampling and shallow coring (up to 6 metres depth) to determine the geometry, facies patterns and internal architecture of a distributary mouth bar. The second phase of this work was done in 1993 and focused on the crest of the active distributary mouth bar to determine the detailed facies pattern, reservoir architecture and heterogeneity within the bar. The lengths of the vibracores used in this work were insufficient to determine in detail the thickness and geometry of the bar system. Therefore, coring campaign was again conducted in 1997, with drilling platform capable of drilling to depths of 20 m.Results of several studies conducted in the modern Mahakam sediments were then compared with facies analysis of the Miocene cores to understand any differences in terms of depositional energy between the modern and the Miocene sediments.